Gene expression of extracellular-signal regulated protein kinase 1/2 and their MAPKKs in hypertrophic scars - Chen, Wei (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2003)
OBJECTIVE: To explore the change of extracellular-signal regulated protein kinase 1/2 (ERK1/2) and their mitogen activated protein kinase kinases(MAPKKs) gene expression in normal skins versus hypertrophic scars underlying their biological significances